Robert Ludlum's The treadstone transgression [large type] - Hood, Joshua; Ludlum, Robert, 1927-2001 (Hood, Joshua. Treadstone series, 2022)
"The most pressing issue on Adam Hayes's mind is planning his son's upcoming fifth birthday party. After years of operating in the world's most dangerous spots for Treadstone, he's ready to call it quits, but Levi Shaw, Treadstone's director, calls Hayes back for one more mission. "It's a walk in the park. You don't even have to go in with the strike team. I just need you to set up the safe house. You'll be home in time to pick up the birthday cake." But when the mission is blown, only Hayes is left alive, and everyone, it seems, is determined to correct that oversight"--